System-Level Signal Analysis Methodology for Optical Network-on-Chip Using Linear Model-Based Characterization - Kim, Min Su; Kim, Yong Wook; Han, Tae Hee (IEEE transactions on computer-aided design of integrated circuits and systems, 2020)
State-of-the-art silicon photonics technology has demonstrated its potential use in all required building blocks for ultrahigh bandwidth on-chip optical links. However, a robust system-level abstraction model reflecting the properties of optical devices has not been well established. We propose a linear optical device model (LODM) for silicon photonic devices and an associated computation method of optical signal propagation (CMOP) in an optical network-on-chip (ONoC). The CMOP manipulates the optical signal routing paths according to the topology, router configuration, and routing algorithm of the given ONoC architecture; thus, it allows the transformed information to be adaptable in an LODM to facilitate simplified analysis. Furthermore, we construct a linear system model of a microring resonator (MR) to reduce the computation complexities caused by its resonance structure. By using the CMOP, we accelerate the system-level analysis of optical signal propagation in ONoCs, reflecting the propagation loss, interference, and phase shift with close accuracy to analog and mixed-signal extensions (AMS) environments. The evaluation results show that the computation speeds up by three orders of magnitude with 1.57% error in accuracy when compared to the AMS environments.